The post-adoption of radio-frequency identification technology in omnichannel retail, manufacturing, and supply chain: essays on the accounting information improvement for corporate reports - Iguma, Marcio Kawahara (2024)
Radio-frequency identification (RFID) is an automatic identification and data capture technique that represents one of the core technologies for the Internet of Things and Industry 4.0. RFID systems provide amounts of real-time data for more accurate analysis in big data, artificial intelligence, cloud computing, and blockchain applications. Despite the relevance of RFID technology, there is a lack of empirical studies on the influences of digital technologies on omnichannel retailing, manufacturing, supply chain, and accounting. This doctoral dissertation is organized into three essays that jointly contribute to the general purpose of examining not only the contextual factors (antecedents) but also the benefits (consequences) of the RFID assimilation process in organizations. The first essay uses an exploratory multiple case study design based on qualitative research with three large omnichannel retailers of the fashion industry, that are listed companies in B3 (Brazil\'s stock exchange), while the pilot case is a porcelain manufacturer. The findings revealed that the RFID system allows full inventory counts with agility, safety, and accuracy, much more frequently than traditional cyclical counts. The most relevant change in accounting practices refers to the recognition and provision of losses that enhance the accounting information quality. The second essay is an in-depth single case study with a garment manufacturing company in the omnichannel supply chain of fashion retailers. The case is one of the few garment manufacturers in the country that successfully adopted item-level RFID in the assembly line to control its internal operations. The results show that RFID improved information sharing in three levels of integration in the supply chain: internal, supplier, and customer. RFID contributed to the accounting practices related to work-in-progress and finished goods inventories, cost accounting, and loss recognition, thus improving the measurement of items in stock, the cost of goods sold, and, consequently, the results in financial reports. The third essay is quantitative research using a cross-sectional survey to investigate RFID assimilation by companies from different industry sectors in Brazil. The target population of this study consists of managers and decision-makers with expertise in RFID applications in the supply chain, logistics, and inventory management areas. The contextual factors influenced the three stages of RFID assimilation (initiation, adoption, and routinization) in different ways, while the influences on information sharing and the quality of accounting information varied through these stages. We found evidence that the three-stage model provides valuable insights compared to a dichotomous adoption/non-adoption model. Finally, this study contributes to theory by proposing an interdisciplinary theoretical framework that integrates information systems, supply chain management, and accounting concepts. We hope our dissertation opens new paths in different research areas, especially in financial and management accounting fields. This research identified a recent and not yet researched phenomenon: the assimilation of RFID by retailers, manufacturers, and other sectors in Brazil. Thus, it also contributes to practice, offering guidance and insights into the successful adoption and use of RFID technology in organizations.